From Pre-Service to Novice: Unraveling EFL Teachers’ Professional Identity Transformation through the Lens of Critical Incident Technique - Fidelis Elleny Averina; Paulus Kuswandono (Jurnal Sinestesia, 2022)
While it has been widely acknowledged by previous researchers that professional identity transformation was considered to be one of the most susceptible stages for EFL teachers, very few of them analysed it through the lens of critical incident technique in the Indonesian context. Thus, to fill the gap in the literature, this study aimed to explore novice EFL teachers’ identity in the pre-service stage and the ways they mediated the tensions encountered during their early careers to transform their professional identity. Critical Incident Technique (CIT) was employed as a method in this study by utilizing an open-ended questionnaire and in-depth interview to gather the data and ensure triangulation. Eight novice EFL teachers from different regions in Indonesia were purposefully selected as the participants. The result revealed that the teacher as a facilitator became the most dominant imagined professional identity possessed by the participants in the pre-service stage followed by the teacher as a moral guide and the teacher as a language expert. As for participants’ designated identity in the novice stage, five salient notions were identified. They are the teacher as an adaptive agent, becoming an authentic and a genuine teacher, the teacher’s sense of belonging within the community of practice, embracing the teacher’s vulnerability, and the teacher as an autonomous lifelong learner.